Challenges of Undergraduate Students in Speaking English at United College (United Journal of Interdisciplinary Studies, 2024)
This study aims to analyze the challenges of undergraduate students in speaking English at United College. Quantitative research approach and a correlational research design were employed. A total of 64 students participated in the study, selected based on their weak performance in English class presentations. A close-ended questionnaire was distributed, and data were collected using a drop-up-pick- up method. Descriptive and inferential statistics, including regression analysis, were utilized for comprehensive data analysis. The findings revealed that fear of making mistakes and limited vocabulary and grammar knowledge significantly influence difficulties in speaking English, emphasizing the need to address psychological barriers and enhance linguistic competencies. Limited exposure to English was also identified as a significant factor contributing to speaking difficulties. However, hypotheses related to lack of practice and cultural barriers were rejected. These findings provide valuable insights into the multifaceted nature of factors influencing language acquisition among undergraduate students. Therefore, it is recommended to implement targeted interventions addressing psychological barriers, such as fear of making mistakes, and to enhance vocabulary and grammar knowledge through structured language enrichment programs, while also increasing students' exposure to English through immersive experiences and integrating regular speaking practice into the curriculum.